Risk of venous thromboembolism in people with lung cancer: a cohort study using linked UK healthcare data - Walker, Alex J.; Baldwin, David R.; Card, Timothy R.; Powell, Helen A.; Hubbard, Richard B.; Grainge, Matthew J. (Cancer Research UK, 2016)
Background: Venous thromboembolism is a potentially preventable cause of death in people with lung cancer. Identification of those most at risk and high risk periods may provide the opportunity for better targeted intervention.